RBM-5 modulates U2AF large subunit-dependent alternative splicing in C. elegans. Issue 10 (3rd October 2018) - Zhou, Chuanman; Gao, Xiaoyang; Hu, Surong; Gan, Wenjing; Xu, Jing; Ma, Yongchao C.; Ma, Long
ABSTRACT: A key step in pre-mRNA splicing is the recognition of 3ʹ splicing sites by the U2AF large and small subunits, a process regulated by numerous trans -acting splicing factors. How these trans -acting factors interact with U2AF in vivo is unclear. From a screen for suppressors of the temperature-sensitive (ts) lethality of the C. elegans U2AF large subunit gene uaf-1(n4588) mutants, we identified mutations in the RNA binding motif gene rbm-5, a homolog of the tumor suppressor gene RBM5. rbm-5 mutations can suppress uaf-1(n4588) ts-lethality by loss of function and neuronal expression of rbm-5 was sufficient to rescue the suppression. Transcriptome analyses indicate that uaf-1(n4588) affected the expression of numerous genes and rbm-5 mutations can partially reverse the abnormal gene expression to levels similar to that of wild type. Though rbm-5 mutations did not obviously affect alternative splicing per se, they can suppress or enhance, in a gene-specific manner, the altered splicing of genes in uaf-1(n4588) mutants. Specifically, the recognition of a weak 3ʹ splice site was more susceptible to the effect of rbm-5 . Our findings provide novel in vivo evidence that RBM-5 can modulate UAF-1-dependent RNA splicing and suggest that RBM5 might interact with U2AF large subunit to affect tumor formation.